SERUM PENTRAXIN-3 (PTX3) LEVEL AS IN-HOSPITAL MAJOR CARDIOVASCULAR EVENTS PREDICTOR IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Fildzah Yamami Rizal, Refli Hasan, Ali Nafiah Nasution , Abdul Halim Raynaldo , Teuku Bob Haykal & Harris Hasan (International Journal of Research Science and Management, 2019)
Background: Acute myocardial infarction is a condition caused by ruptured of atherosclerotic plaque. Atherosclerosis is an inflammation process since formation until acute coronary syndrome events. Pentraxin-3 (PTX3) is an acute phase glycoprotein which secreted by haemopoietic and endothelial cells. PTX3 in early phase of acute myocardial infarction was found to be a prognostic marker in patients with myocardial infarction. Method: This is a prospective cohort study, in 87 consecutively acute myocardial infarction patients in Adam Malik General Hospital Medan. Serum PTX3 levels were checked on admission at Emergency Room. All patients were observed during hospitalization to determine major cardiovascular events (MACE) including acute heart failure, cardiogenic shock, arrythmia, and death. Data were analysed using SPSS version 24. Results: Serum PTX3 levels were significantly higher in acute myocardial infarction with MACE than in events free patients (p < 0.001) with median of 4.45 (0.29-10.76) ng/mL. Using ROC curve, the optimal cut-off value was 3,61ng/mL for predicting MACE with a sensitivity of 63 % sensitivity and specificity of 72%. In multivariate logistic regression analysis, serum PTX3 levels with OR value of 1,388 (95% CI 1,142-1,686 ; p value 0,001) independently predicted MACE along with sex, heart rate, symptom onset and GRACE score. Conclusion: Serum PTX3 predicted in-hospital MACE and might be used as a marker to determine high-risk patients with acute myocardial infarction.